WATER-ENERGY-FOOD NEXUS IN THE PIRACICABA, CAPIVARI, AND JUNDIAÍ RIVER BASINS (PCJ) UNDER HISTORIC CONDITIONS AND CLIMATE CHANGE PROJECTIONS - Da Silva, Tamires Lima [UNESP]; Román, Rodrigo Máximo Sánchez [UNESP]; Sarjoughian, Hessam S.; Fard, Mostafa D. (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2024)
The water-energy-food (WEF) nexus approach promotes integrated management and governance across scales and sectors to achieve sustainable socioeconomic development. This study aimed to model the WEF nexus in the Piracicaba, Capivari, and Jundiaí (PCJ) river basins under historical conditions and future climate scenarios. Models were developed using WEAP and LEAP programs, covering the period from 1995 to 2019 for historical conditions and from 2020 to 2070 for climate projections. The WEAP-KIB-LEAP framework enabled data exchange between WEAP and LEAP to model interactions effectively. In WEAP, the projected impacts of climate change on streamflow in the PCJ basins were modeled using data from the Eta Regional Climate Model under RCP4.5 and RCP8.5 scenarios. The findings indicate that, in future scenarios, hydropower generation will be compromised, while water and electricity demand for irrigation will increase by 35.6% and 82.7%, respectively, driven by a projected food production growth of 21.3%. These results highlight the interdependence between water, energy, and food resources in the PCJ basins.
NEXO ÁGUA-ENERGIA-ALIMENTO NAS BACIAS HIDROGRÁFICAS DOS RIOS PIRACICABA, CAPIVARI E JUNDIAÍ (PCJ) SOB CONDIÇÕES HISTÓRICAS E DE PROJEÇÕES DE MUDANÇAS CLIMÁTICAS
Keywords: agriculture; irrigation; LEAP; WEAP; WEAP-KIB-LEAP framework